Mobile game development for UTAR Kampar campus touring - Chen, Zhe Sheng (2022)
Most of the campuses of renowned universities have their interesting attractions, and these attractions may also have good stories that are worth visitors exploring. For instance, there are quite many points of interest on UTAR Kampar campus. However, when visitors are visiting the campus, there lacks a good application that is able to introduce the backgrounds and stories of these campus attractions. Therefore, this project intends to use the concept of tourism gamification to attract visitors and promote UTAR Kampar campus with a gamified touring application. An Augmented Reality (AR) game will be developed to interact with the visitors while they are visiting UTAR Kampar campus in order to enhance their touring experience. Moreover, the game will also allow visitors to learn the stories of UTAR Kampar campus, and through playing with the quizzes in the game, the visitors can link the campus attractions together.